Padrões de uso de imagens no gênero artigo acadêmico experimental: uma análise multimodal comparativa entre linguística aplicada e agronomia - Santos, Katia Simonetti dos (2018)
The use of different semiotic resources in the communication of scientific knowledge has increased over the last decades in traditional academic genres, such as the experimental research article. Beyond that, It has also promoted the creation of new genres, such as graphical abstracts (FLOREK, 2015) and audiovisual research articles (SILVA, 2015, SOUZA, 2015, MILANI, 2017). However, the study of patterns in the use of images, as well as the prodution of teaching materials for the formation of multiliterate students represent a research niche that has not been widely focused in genre studies. In this sense, this mater’s study aims at analyzing and contrasting the use of images in experimental research articles (RA) published in the areas of Applied Linguistics (AL) and Agronomy (AGR) in terms of: 1) frequency; 2) occurrence (salience and position) in the genre; 3) nature (for example, tables, figures, etc.); and 4) rhetorical function (eg "presenting the participants", "presenting a concept", etc.) in the sections in which it occurs. In order to answer this objective, we investigated 20 RAs from each area using the theoretical-methodological tools offered by Critical Genre Analysis (CGA) - an interdisciplinary approach that enables the analysis of the intimate relationship between text and context. The results indicated that these two areas have quite different patterns. In relation to frequency, AGR used a great number of images per article (at least four), while in AL the amount of images severely oscillated among the RAs. In relation to occurrence, images in AGR seemed more independent from the verbal semiosis, since, their position showed a more fractional reading - in the poles of the page - or a more contrastive - one on top of the other. In AL, on the other hand, the verbal semiosis defined the position of the images in the text – each image is presented when it is mentioned. In relation to nature, AGR has allocated all images and a plurality of types of information under the 'table' and 'figure' names. AL, however, presented six name variations, as well as two possibilities of omitting the nature of the images. In relation to the rhetorical function, in AGR, images are mandatory in the R/D section, which are crucial to materialize the argument, mostly from quantitative data, in the study. In AL, images are not mandatory to the RA sections, although most of them were found in the R/D section, which emphasize quantitative and qualitative data. The different patterns found in each area were related and explained on the analysis of particular disciplinary traditions. On the one hand, the need to use images has led the area of AGR to create conventions (also in the form of documents) that students are supposed to get engaged in to fully participate in this community of practice. On the other hand, the lack of a convention on the use of images in AL has apparently clarified the plurality of ways to report academic knowledge in form of images. These results aim to contribute to the teaching of reading and production of knowledge in images in RAs, as well as raising questions about the visual practices adopted, mainly in AL.